Characteristics of individuals who received post‐exposure prophylaxis and HIV seroconversion in Malawi: an analysis of national routine HIV testing data - Hannock Tweya; Tiwonge Chimpandule; William Wu; Leah Goeke; Zhouyun Zheng; Stone Mbiriyawanda; Tobias Masina; Washington Ozitiosauka; Martha Muyaso; Anna Drabko; Dominik Bilicki; Jiehua Chen; et al. (Journal of the International AIDS Society)
Abstract Introduction In Malawi, where HIV prevalence remains high at 6.7%, post‐exposure prophylaxis (PEP) has been implemented as one of the HIV prevention strategies. However, there is limited data on the characteristics of PEP users and HIV seroconversion. Using national routine HIV testing services (HTS) programme data, we described the demographic characteristics and risk of exposure to HIV for HTS clients reporting PEP use and determined HIV seroconversion rates among those with baseline HIV‐negative results. Methods We conducted a descriptive cross‐sectional study of individuals aged 2 years and older accessing HTS who reported PEP use. A subset was included in a retrospective cohort to determine HIV seroconversion rates. The risk of exposure to HIV was classified as high, ongoing, low and not assessed. HTS encounters data were extracted from a national HTS data repository. Some HTS clients had multiple HTS encounters. Descriptive statistics were reported for the study populations and Poisson regression model with an offset was used to estimate HIV seroconversion rates. Results Between November 2022 and July 2023, there were 21,298 HTS encounters where PEP use was reported any time prior. Of the 21,298 encounters, 1847 (8.7%) HTS clients with a baseline HIV‐negative status were included in the cohort study component. The median follow‐up time was 30 days (interquartile range 30–61). Of the 1847 HTS clients, 1055 (57.1%) were males and 928 (50.2%) were aged 20 and 29 years. A total of 329 (17.8%) HTS clients reported a high‐risk HIV exposure event in the past 3 months, 581 (31.5%) had an ongoing risk of exposure to HIV, 892 (48.3%) had low risk of exposure to HIV and 45 (2.4%) assessment was not done. Overall, five individuals seroconverted, yielding a seroconversion rate of 2.08 (0.87−4.99) per 100 person‐years. Conclusions The majority of PEP users were young adults and males. A sizeable proportion had an ongoing risk of exposure to HIV. The HIV seroconversion rate was high. Targeted efforts should focus on promoting condom use, encouraging partner testing and expanding access to PEP for those with ongoing HIV exposure.